2021
DOI: 10.3390/ijerph18179279
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Media Exposure on Anxiety and Working Memory during Lockdown Period in Italy

Abstract: The rapid spread of the coronavirus pandemic has caused anxiety around the world. During lockdown, the media became a point of reference for people seeking information. However, little is known on the relationships between anxiety resulting from persistent media exposure to coronavirus-related programs and the effects produced on working memory. In this work, a total of 101 Italian citizens (53.7% female) aged between 18 and 45 years old, who were from 14 provinces in Italy, participated in an online survey. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…In recent years, tests have been conducted in an attempt to investigate various phenomena such as TV addiction [ 2 ], excessive use of computer games [ 3 ], gambling disorders over the web [ 4 ] and, generally, internet addiction [ 5 ]. The excessive use of smartphones, also known as ‘nomophobia’, has proven to be a form of technological addiction that is rapidly becoming a major social problem around the world [ 6 , 7 , 8 , 9 , 10 ]. Today, addiction is defined as a pleasure-inducing behavior that through repeated exposure gradually leads to loss of control and further negative consequences [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tests have been conducted in an attempt to investigate various phenomena such as TV addiction [ 2 ], excessive use of computer games [ 3 ], gambling disorders over the web [ 4 ] and, generally, internet addiction [ 5 ]. The excessive use of smartphones, also known as ‘nomophobia’, has proven to be a form of technological addiction that is rapidly becoming a major social problem around the world [ 6 , 7 , 8 , 9 , 10 ]. Today, addiction is defined as a pleasure-inducing behavior that through repeated exposure gradually leads to loss of control and further negative consequences [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our results suggest that the pandemic did not have an impact on attentional mechanisms, relating either to “emotional” or “non-emotional” stimuli. Previous literature showed that the COVID-19 lockdown was associated with poorer cognitive performance ( 54 , 55 ) and increased attention toward social cues ( 56 ). Our findings seem to go against these results; this discrepancy likely reflects the specific components investigated and the measures used, since previous studies primarily focused on working memory (especially using n-back tasks) or gaze cueing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…When considering our experimental design, it is important to compare the EST to a task that assesses purely cognitive processes, not influenced by emotional or distressing features. Indeed, some studies have shown that COVID-19-related anxiety is associated with poorer cognitive performance ( 54 , 55 ), as well as increased attention toward social cues ( 56 ). One of the most relevant and frequently used approaches to studying visual cognitive processing is through visual search tasks ( 57 , 58 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the performance of working memory (WM), n-back was used, a continuous performance activity commonly adopted in the field of psychology and cognitive neuroscience. This paradigm has been widely used in the literature and has shown good psychometric properties [ 31 , 32 , 33 ]. The n-back task involves the serial presentation of stimuli (for example, an image or a sound), separated from each other by a few seconds.…”
Section: Methodsmentioning
confidence: 99%